“Species imperfecte cognita”—enlightening Paepalanthus cordatus (Eriocaulaceae): nomenclatural and taxonomic notes on an endangered species from central Brazil - Trovó, Marcelo (Phytotaxa, 2021)
Paepalanthus cordatus is an endangered species described from a single collection which lacks fully developed inflorescences and flowers. Despite the absence of these characters, the species was unambiguously placed in P. sect. Diphyomene, one of the few groups of Paepalanthus with dimerous flowers and which is mainly distributed in central Brazil. In this manuscript, I provide a full description of the species, detailing and illustrating the fully developed inflorescences and flowers for the first time. The spherical umbel-shaped inflorescence is composed of sets of capitula bearing dimerous flowers; the pistillate flowers have dolabriform sepals and bifid stigmatic branches; the staminate ones have an elongated fleshy anthophore. These characters fully match the current circumscription of P. sect. Diphyomene. Based on the specimens recently collected and additional data, the new conservation status for the species is Endangered instead of Critically Endangered, as previously assessed. I also clarify the inadvertent lectotype selection and previous interpretations of the type specimens. Comments on the species distribution, morphology, and ecology, as well as a geographic distribution map, photos, and a detailed illustration are also provided.